Wonderland Earth in the Anthropocene Epoch - Rolston, Holmes, 1932-2025, author; Routledge, publisher (Colorado State University. Libraries, 2020)
1. Wonderland planet. In the cosmos, remarkable features produce billions of stars generating elements suitable for life. Life is so far known only on Earth. Humans result from a cosmic "anthropic" principle. 2. Humans - the wonder of wonders. The human mind is by far the most complex thing known, capable of semantic and symbolic speech, elaborating high orders of rational and emotional thought in science, philosophy, ethics, art, and religious faith. 3. Wondering about Anthropocene Humans? Humans have gained vast powers for transforming their planet. Human dominance is so extensive that Earth has apparently entered the Anthropocene Epoch. 4. Managed Planet and End of Nature? Enthusiasts advocate that human ought to engineer Earth resourcefully, increasing their dominion, bringing about the end of nature. The Anthropocene is "humanity's defining moment." 5. Anthropocene Arrogance. Critics wonder. Ought not this sole moral species do something less self-interested than value Earth's wonders only for the benefits they bring? 6. Wonderful Humans Incarnate on Wonderland Earth. A better hope is for a tapestry of cultural and natural values, not a trajectory even further into the Anthropocene. Cherish wonderful humans incarnate on wonderland Earth.
Keywords: wonderland Earth; Anthropocene Epoch; end of nature; managed planet; natural values; cultural values; human excellence